GATT and the “Uruguay Round” - Rudolf Adlung (Intereconomics, 1987)
In September 1986, a ministerial conference staged in Punta del Este, Uruguay, gave the starting signal for a new GATT round. This round will be a test of the adaptability and reformability of the multilateral trading system. The following article examines the issues involved and the ensuing conflicts, of interest.
Keywords: 330; Trade Policy